Optimizing Tahsinul Qira'at Management Using the Wafa Method in Improving Santri's Reading at Ma'had Baitul Qur'an Madura - Fathurrozi, Fathurrozi; Bari, Abdul; Astutik, Fitriyah Ika (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2025)
This study examines the optimization of Tahsinul Qira'at management through applying the Wafa method at Ma'had Baitul Qur'an Madura using a qualitative approach of case study type. This design was chosen to understand managerial practices in the natural context of pesantren, which are rich in values, traditions, and distinctive dynamics. Data was collected through in-depth interviews with caregivers, musyrif, and santris, as well as field observations and documentation studies. Data analysis was conducted interactively, using the steps of reduction, presentation, and conclusion drawing, while data validity was maintained through the triangulation of sources and techniques. The results showed that Tahsinul Qira'at management was optimized through three main stages: planning, implementation, and evaluation. Planning is organized through deliberation between managers and teachers, including class structure, teacher allocation, and periodic assessment. In implementation, the Wafa method is used as the main approach with the flexibility of additional methods according to the needs of the students. Learning is carried out in three daily sessions with efficient time management. Evaluations are conducted weekly and monthly as a means of monitoring and continuous guidance on the quality of santri reading. Some obstacles are still faced, such as the limited number of musyrifs, variations in students' ability, and class dynamics that are not always conducive. These findings make a practical contribution to developing Qur'anic education management in pesantren and enrich the academic literature on integrating educational management and pedagogical strategies based on the Wafa method.